2020
DOI: 10.1186/s13023-020-01578-3
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of inherited metabolic disorders in southern Israel: a comparison between consanguinity and non-consanguinity communities

Abstract: Background Inherited metabolic disorders (IMDs) are group of rare monogenic diseases, usually derived from reduced or absent activity in a single metabolic pathway. Most of the IMDs are inherited in an autosomal recessive manner. The incidence of IMDs varies from country to country and within different ethnic groups, but data is still scarce. Consanguinity rate among populations is highly contributor factor for IMDs incidence. There are no reports comparing the incidence of IMD in consanguineous and non-consan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…The incidence of the IEM that we have described in our study is in accord with that reported by Hazan et al (2020) . Due to the high rate of consanguinity, the Negev region has a substantially higher incidence of IEM than the reported global incidence ( Waters et al, 2018 ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The incidence of the IEM that we have described in our study is in accord with that reported by Hazan et al (2020) . Due to the high rate of consanguinity, the Negev region has a substantially higher incidence of IEM than the reported global incidence ( Waters et al, 2018 ).…”
Section: Discussionsupporting
confidence: 92%
“…A plausible explanation for the significant differences in the incidence of the diseases would be related to the composition of the populations included in each study. The majority of women included in our study were of Bedouin origin, who are known to have a higher consanguinity rate, as reported previously (Hazan et al, 2020). In their study, Moammar et al (2010) discussed the incidence of IEM in the Eastern Province of Saudi Arabia, where there is a high consanguinity rate, and families tend to have more children, similar to the Bedouin population in the Negev region of Israel; the incidence of the same three groups of IEM in their study was LSD 44 per 100,000, mitochondrial diseases 8 per 100,000, and GSD 10 per 100,000, which with the exception of LSD incidence, are quite similar to our report.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Therefore, our results may not accurately reflect the urban and rural distribution of IMDs in the Suqian area. Besides, this study could not provide detailed information on the routine biochemistry of patients and their mothers (Bower et al, 2019;Hazan et al, 2020;Raskind and El-Chaar, 2000;Scriver et al, 2001;Tebani et al, 2016;The People's Government of Jiangsu Province, 2019). participated in its design and coordination, and wrote the manuscript.…”
Section: Discussionmentioning
confidence: 95%
“…Closer prenatal follow-up and appropriate genetic consultation after the delivery or diagnosis of either patient V2 or V6 is warranted, especially with the consanguinity in this extended Bedouin family. However, due to cultural beliefs no genetic consultation was performed before patient V3 was born, and she was diagnosed by NBS with a high index of suspicion, like patient V14, who was born before the extended Israeli NBS was started and presented later in life [27].…”
Section: Discussionmentioning
confidence: 99%